The future of tax services: Coretax as a technology-based breakthrough - Rizky, Annur Muhammad; Nurhidayat, Muhamad Rifqi; Yasar, Muhammad Miftah Babil (WIM Solusi Prima, 2025)
This study aims to evaluate the implementation of the Coretax Administration System (Coretax) as a form of digitization of the tax administration system in Indonesia. The method used is a qualitative descriptive approach with purposive sampling techniques, involving four main groups of informants: Directorate General of Taxes (DJP) employees, academics, tax consultants, and business actors. The research focuses on analyzing technological readiness, supporting and inhibiting factors in implementation, and perceptions of Coretax 's effectiveness. The results show that the system has sufficient technological readiness, supported by cutting-edge features such as the use of artificial intelligence (AI) and big data. In addition, Coretax is considered capable of improving service efficiency, taxpayer compliance, and contributions to state revenue. However, challenges remain in the form of suboptimal system stability, limited digital literacy among users, and the lack of comprehensive integration of all tax administration processes. The study recommends improving technological infrastructure, providing digital education for users, expanding system integration, and further leveraging AI technology to realize Coretax as an inclusive, sustainable, and globally standardized digital tax system.